Diagnostic accuracy of molecular testing with three molecular markers on thyroid fine‐needle aspiration cytology with abnormal category. Issue 6 (7th February 2020) - Seneldir, Hatice; Kir, Gozde; Soylemez, Tuce; Girgin, Rabia B.; Ozbay, Nurver; Ozen, Filiz; Ankarali, Handan; Bas, Gurhan; Alimoglu, Orhan
Abstract: Background: Cases with abnormal category, determined by thyroid fine‐needle aspiration (FNA), frequently undergo surgical resection, despite the majority of cases being identified as benign after resection. Additional diagnostic markers are needed to guide the management of patients with abnormal thyroid nodules. Materials and Methods: The retrospective study enrolled 150 cases diagnosed abnormal by FNA cytology that had undergone molecular testing with three markers (BRAF V600E, NRAS, and KRAS) on the cell block. Seventy‐one cases had a surgical follow‐up. Results: When NIFTP is not considered as malignant, positive predictive values (PPVs) of cytology and combined cytology and molecular testing (CC‐MT) were 67.6% (95% CI: 0.555‐0.782) and 89.2% (95% CI: 0.746‐0.970) ( P = .004), respectively. The sensitivity of the CC‐MT was 68.8%, specificity was 82.5%, and the false‐positive rate was 17.4%. When NIFTP is considered as malignant, PPVs of cytology and CC‐MT were 83.1% (95% CI: 0.743‐0.918) and 94.6% (95% CI: 0.873‐1.018) ( P = .047), respectively. The sensitivity of the CC‐MT was 59.3%, specificity was 83.3%, and the false‐positive rate was 16.7%. Conclusion: The addition of molecular testing with a small panel to FNA cytology may increase the PPV of cytology in abnormal categories. Small panel (BRAF V600E, KRAS, and NRAS) with high specificity and high PPVs may be used particularly for the detection of thyroid malignancy. Cell blocks can be an especially useful and straightforward method for molecular diagnostic studies.